#84: Evolutionary Pressure from APOBEC Causes an Underrepresentation of TC Motifs in Human Polyomavirus. (26th March 2021) - Shapiro, Kate; Shapiro, Maxwell; MacCarthy, Thomas
Abstract: Background: Apolipoprotein B mRNA editing enzyme, catalytic polypeptide-like (APOBEC) is a family of enzymes found in mammals that deaminate cytidine to uridine on ssDNA, facilitating a C-to-T mutation. Less commonly, APOBEC effectively mutates C-to-G as well. APOBEC has the potential to mutate the viral genome, rendering the virus nonproductive. The enzyme targets certain mutational motifs, also known as hotspots: most APOBECs deaminate at TC motifs. We hypothesize that human polyomaviruses (hPyV) have an under-representation of TC hotspots in their genomes to avoid APOBEC targeting. Specifically, we analyzed the degree of TC motif under-representation in five conserved genes of hPyV, each of which is expressed in either the early or late phase of the viral life cycle. Methods: We utilized a statistical tool, the Cytidine Deaminase Under-representation Reporter (CDUR) that can be used to analyze sequences and determine whether these sequences have mutated under the evolutionary pressure of APOBEC based on the targeted hotspot. This tool uses a permutation test to determine whether the number of hotspots at a given coding sequence is significantly more or significantly less than expected under pseudo-random biological sequence evolution. The same analysis was used to determine whether the number of nonsynonymous mutations that might occur at those hotspots is significantly more or significantly less than expected by chance. Results: TC motifs in early genes were more underrepresented compared with late genes in most hPyV species. Most early genes were susceptible to nonsynonymous mutations at the TC motifs. Those species which did not fit into this paradigm showed a similar degree of under-representation and susceptibility to nonsynonymous mutations at AC motifs. We also find a large over-representation of TG hotspots, but not TT hotspots. Conclusions: hPyV may have evolved a reduced number of hotspots to subvert APOBEC and evade host immune defenses. Under-representation of TC motifs is more prevalent in early genes. Early genes include the small T and large T antigens, essential for viral proliferation. In addition, the large T antigen was particularly susceptible to mutation at TC motifs. This underscores the evolutionary pressure imposed on hPyV by APOBEC to evade host immunity. It is possible that the over-representation of TG motifs in hPyV is due to specific host DNA-repair mechanisms, but this requires further investigation.